2009
DOI: 10.1634/theoncologist.2009-0056
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Attitudes on the Use of Adjuvant Chemotherapy and Trastuzumab in Older Adults with HER-2+ Breast Cancer: A Survey of Oncologists

Abstract: Background. Substantial evidence supports the use of adjuvant trastuzumab with chemotherapy for patients with human epidermal growth factor receptor (HER)-2 ؉ breast cancer; however, a lesser amount of data is available to guide use of this therapy in older patients and in those with significant medical comorbidities. The goal of the current study was to understand how patient age and health status impact oncologists' decisions to recommend adjuvant therapy in older women with HER-2 ؉ breast cancer.Methods. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our data show that the decision to take this treatment approach is clearly associated with expected characteristics, such as older age or worse general health status, and less aggressive histology, rather than tumor stage. These results from real-world data reflect findings for hypothetical cases presented to US oncologists in a survey asking for treatment recommendations in older adults with HER2-positive EBC [ 24 ].…”
Section: Discussionsupporting
confidence: 71%
“…Our data show that the decision to take this treatment approach is clearly associated with expected characteristics, such as older age or worse general health status, and less aggressive histology, rather than tumor stage. These results from real-world data reflect findings for hypothetical cases presented to US oncologists in a survey asking for treatment recommendations in older adults with HER2-positive EBC [ 24 ].…”
Section: Discussionsupporting
confidence: 71%
“…While prognostic models have included age as an adverse factor in lymphomas (The International Non‐Hodgkin's Lymphoma Prognostic Factors Project, ; Solal‐Celigny et al , ), studies that have led to this conclusion included few patients >80 years and were conducted before the modern chemoimmunotherapy era. Whether old age affects outcome due to different disease biology in the elderly or due to older patients being treated less aggressively remains unknown (Hurria et al , ). Another factor that could affect outcome in the elderly patient population is dose density and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses using the acquired dataset have explored differences in treatment recommendations amongst these two respondent categories, and have further addressed oncologists’ recommendations for patients with HER2-overexpressing disease. 18,19 In the current analysis, responses from oncologists were assessed with respect to treatment recommendations for hormone receptor positive, non-HER2-overexpressing disease. Candidates for the survey study were identified using the American Medical Association (AMA) member database.…”
Section: Methodsmentioning
confidence: 99%